Utilization of Recycled Glass as an Alternative to Silica Sand Filter Media in Reducing Total Suspended Solids (TSS), Turbidity, and Phosphates in Laundry Wastewater - Wicaksono, Pandu; Firra Rosariawari (Jurnal Serambi Engineering, 2025)
This study examines the comparative performance of recycled glass and silica sand as filter media in the slow sand filtration process to treat laundry wastewater. The main objective of this study was to evaluate the efficiency of recycled glass and silica sand in reducing Total Suspended Solids (TSS), turbidity, and phosphate content in laundry wastewater effluent. The selection of recycled glass as a filtration medium is due to its characteristic of having a small sphericity value so that its porosity value is large which results in a small headloss value. The use of recycled glass as an alternative media is an effort to reduce the exploitation of the use of sand media in filtration. The results of the study showed that the use of recycled glass was quite efficient than silica sand in reducing TSS and turbidity with a percentage of TSS removal (94%% vs 90%) and turbidity (90,57% vs 86,04%). While in phosphate removal, silica sand was more efficient than recycled glass with a percentage of removal (46,74% vs 83,48%). Before the research was conducted, a maturation phase was carried out for 2 weeks to form the schmutzdecke layer. The addition of Effective Microorganism 4 (EM4) was carried out to help the growth of the schmutzdecke layer in this study.